Human Rights in the Trade and Sustainability Impact Assessment of the EU–Tunisia Free Trade Agreement. (2nd April 2018) - Walker, Simon
Abstract: This article critically examines the integration of human rights in the trade and sustainability impact assessment of the proposed Deep and Comprehensive Free Trade Agreement between the EU and Tunisia. The main contribution of this article is to list the basic requirements of a human rights impact assessment methodology in the form of a list of questions as a means to evaluate impact assessments of trade agreements. Using this list, the article demonstrates how the EU–Tunisia assessment meets many of the formal requirements of human rights impact assessment but that the underlying human rights analysis and recommendations were weak and that the approach to consultation and participation of individuals and groups in the assessment process needs review and strengthening. The article recommends the continued professionalization of human rights impact assessment of trade agreements and concludes by noting that the 2015 adoption by the European Commission of Guidelines on the analysis of human rights impacts in impact assessments of trade-related policy initiatives provides a clearer framework to guide and improve future assessments.